Patterns and Determinants of Double-Burden of Malnutrition among Rural Children: Evidence from China - Zhang, Nan (PLoS One, 2016)
Chinese children are facing dual burden of malnutrition—coexistence of under-and over-nutrition. Little systematic evidence exists for explaining the simultaneous presence of under-and over-nutrition. This study aims to explore underlying mechanisms of under-and over-nutrition among children in rural China. This study used a nationwide longitudinal dataset of children (N = 5,017) from 9 provinces across China, with four exclusively categories of nutritional outcomes including under-nutrition (stunting and underweight), over-nutrition (overweight only including obesity), paradox (stunted overweight), with normal nutrition as reference. Multinomial logit models (Level-1: occasions; Level-2: children; Level-3: villages) were fitted which corrected for non-independence of observations due to geographic clustering and repeated observations of individuals. A mixture of risk factors at the individual, household and neighbourhood levels predicted under-and over-nutrition among children in rural China. Improved socioeconomic status and living in more urbanised villages reduced the risk of stunted overweight among rural children in China. Young girls appeared to have higher risk of under-nutrition, and the risk decreased with age more markedly than for boys up to age 5. From age 5 onwards, boys tended to have higher risk of under-nutrition than girls. Girls aged around 12 and older were less likely to suffer from under-nutrition, while boys’ higher risk of under-nutrition persisted throughout adolescence. Children were less likely to suffer from over-nutrition compared to normal nutrition. Boys tended to have an even lower risk of over-nutrition than girls and the gender difference widened with age until adolescence. Our results have important policy implications that improving household economic status, in particular, maternal education and health insurance for children, and living environment are important to enhance rural children’s nutritional status in China. Investments in early years of childhood can be effective to reduce gender inequality in nutritional health in rural China.